Монгол хэлний өгүүлбэрийн утгын харьцаа: Meaning relations of sentences in Mongolian language - Б., Мөнгөнцэцэг (Mongolian Studies, 2023)
Nowadays, semantic study of language is developing that is giving chances to study semantic structures and types in elements of language. It is concerned with study of assimilation and dissimilation language elements which has different structures. According to some language facts, based on the relation which the sole or small parts of speech can compromise the complex or bigger parts while the bigger parts include the smaller, it can be seen that relation in sentence meaning in Mongolian language.